2009
DOI: 10.1016/j.pmrj.2009.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐articular Pressure Profiles of Painful Stiff Shoulders Compared With Those of Other Conditions

Abstract: The steeply rising, high IA pressure can be considered as a predominant characteristic of the PSS compared with other conditions that showed flat, low-pressure profiles, suggesting the P-V profiles might be used in evaluation of the capsular tightness of various shoulder problems. The triphasic curve appears to be a preruptural sign; however, there are several practical limitations to terminating hydraulic distension before rupture occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 35 publications
1
43
1
Order By: Relevance
“…PSS was diagnosed if the shoulder ROM was limited in at least two directions for more than 1 month. ROM was determined as limited for each direction, if abduction < 80°, forward flexion < 130°, external rotation < 30° when measured by goniometer, or if external rotation ≥ C7, internal rotation ≤ L1 by scratch test 18, 19. Patients were excluded if they had any structural or systemic disorder that could result in pain or ROM limitation, such as inflammatory joint disease, osteoarthritis evidenced on radiographs, full‐thickness rotator cuff tear shown by ultrasound imaging, or history of major trauma or surgery involving the shoulder.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PSS was diagnosed if the shoulder ROM was limited in at least two directions for more than 1 month. ROM was determined as limited for each direction, if abduction < 80°, forward flexion < 130°, external rotation < 30° when measured by goniometer, or if external rotation ≥ C7, internal rotation ≤ L1 by scratch test 18, 19. Patients were excluded if they had any structural or systemic disorder that could result in pain or ROM limitation, such as inflammatory joint disease, osteoarthritis evidenced on radiographs, full‐thickness rotator cuff tear shown by ultrasound imaging, or history of major trauma or surgery involving the shoulder.…”
Section: Methodsmentioning
confidence: 99%
“…While the patient was seated on a stool, one of the authors (SGC) inserted a 3.5″ 22 gauge spinal needle, 1 cm lateral to the transducer and advanced it into the posterior intraarticular space under ultrasound guidance 18, 19. The needle was connected to a disposable pressure sensor (AMK 150; ACEMEDICAL, Seoul, Korea) and a 50‐ml syringe via a 3‐way stopcock.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the intra-articular space pressure was not measured objectively, which created uncertainty about whether the fluid volume during IHD was determined at its maximum effectiveness. Finally, the average volume injected in this study was smaller than that reported in the original article by Chung et al [30]. Further studies are needed to resolve these limitations.…”
Section: Discussionmentioning
confidence: 55%
“…However, it is controversial as to whether the volume determined by this method was the maximum volume before capsular rupture would occur. Chung et al [30] used a real-time pressure monitoring device to determine the volume (or to find pre-rupture signs) and eventually suggested 24.4 AE 8.9 mL as an average rupturing volume for patients with a painful stiff shoulder. The mean distension volume in this study was 20.2 AE 5.2 mL for the hypertonic saline group and 19.5 AE 5.9 mL for the normal saline group.…”
Section: Discussionmentioning
confidence: 99%